Validation of magnetic resonance elastography plus fibrosis‐4 for significant fibrosis in nonalcoholic fatty liver disease. Issue 9 (3rd June 2022) - Inada, Kento; Tamaki, Nobuharu; Kurosaki, Masayuki; Kirino, Sakura; Yamashita, Koji; Hayakawa, Yuka; Higuchi, Mayu; Takaura, Kenta; Kaneko, Shun; Maeyashiki, Chiaki; Yasui, Yutaka; Tsuchiya, Kaoru; et al.
Abstract: Background and Aim: MEFIB (the combination of magnetic resonance elastography [MRE] ≥ 3.3 kPa and fibrosis‐4 (FIB‐4) ≥ 1.6) is useful for detecting patients with significant fibrosis (fibrosis stage ≥ 2) having nonalcoholic fatty liver disease (NAFLD). However, age‐dependent thresholds of FIB‐4 have been proposed, and it remains unclear whether MEFIB could be applied with the same FIB‐4 threshold in a different cohort. Therefore, in this study, we examined the best threshold of FIB‐4 and validated the utility of MEFIB. Methods: This study included 105 biopsy‐proven NAFLD patients with contemporaneous MRE assessment. The primary outcome was a diagnostic accuracy for significant fibrosis. Results: The median (interquartile range) age was 65 (58–72) years, and significant fibrosis was 76.2% (80/105). FIB‐4 of 2.1 was defined as the best threshold for significant fibrosis in the cohort. The area under the receiver operating characteristics curves (AUROCs) of the combination of MRE and FIB‐4 (MRE ≥ 3.3 kPa + FIB‐4 ≥ 1.6: 0.80, MRE ≥ 3.3 kPa + FIB‐4 ≥ 2.1: 0.84) were higher than those of each index alone (MRE ≥ 3.3 kPa: 0.76, FIB‐4 ≥ 1.6: 0.72, and FIB‐4 ≥ 2.1: 0.77), but AUROCs of MRE ≥ 3.3 kPa + FIB‐4 ≥ 1.6 and MRE ≥ 3.3 kPa + FIB‐4 ≥ 2.1 were equivalent ( P  = 0.3). Conclusions: MEFIB is useful for detecting patients with significant fibrosis and could be utilized in a different cohort without changing the threshold of FIB‐4, and it may then be used as a two‐step screening strategy.